(3QSGdI GdYdhe ef YbGFO YdeGA GdQShes - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3heeG McGg GdTjN GdCcHQ eMji GdOjf GHf GdYQHi GdWGFi GdGfOdSi GdMGJei ai QSGdI SeGgG QSGdI GdYdhe ef YbGFO YdeGA GdQShe Cfg ELJeY CQHYI faQ ef GdYdeGA ai bHI CQjf JMJ NW GdGSJhGA s
(3BNQgG (B:s
(3Ke GdJaJ ade CQ CMOkG hdG CSeY gGJakG hbGd GdLjdi ai Gdcga hGdQbje TYQkG hZfGfG eZfi Gdbhe hcfG MjK eG cGfhG hcGfhG MjK eG cfG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs